2008
DOI: 10.1002/lsm.20673
|View full text |Cite
|
Sign up to set email alerts
|

Vascular effects of photodynamic and pulsed dye laser therapy protocols

Abstract: Background and Objective-Pulsed dye laser (PDL) treatment of cutaneous vascular lesions is associated with variable and unpredictable efficacy. Thus, alternative treatment modalities are needed. Previous in vitro and in vivo studies have demonstrated enhanced selective vascular destruction with benzoporphyrin derivative (BPD) monoacid ring A photodynamic therapy (PDT) followed immediately by PDL irradiation (PDT+PDL). Here, we evaluate PDT alone, PDL alone, and PDT+PDL protocols using an optimized in vivo rode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
0
26
0
6
Order By: Relevance
“…In all cases, both vascular perfusion and velocity of blood flow increased immediately after PDT and returned to baseline values within several hours to months post-PDT 202,203,207,208. These examples used superficial tissue samples including skin cancers202,203 and dorsal skin-fold chambers 207,208. Angiography has long been used to monitor choroidal neovascularization from age-related macular degeneration 164–166,209.…”
Section: Imaging For Planning Assessment and Monitoring Of Photomentioning
confidence: 99%
“…In all cases, both vascular perfusion and velocity of blood flow increased immediately after PDT and returned to baseline values within several hours to months post-PDT 202,203,207,208. These examples used superficial tissue samples including skin cancers202,203 and dorsal skin-fold chambers 207,208. Angiography has long been used to monitor choroidal neovascularization from age-related macular degeneration 164–166,209.…”
Section: Imaging For Planning Assessment and Monitoring Of Photomentioning
confidence: 99%
“…The U.S. Food and Drug Administration approved by BPD for the treatment of wet age-related macular degeneration, skin carcinoma, and brain tumors. With a series of preclinical studies [8891], we demonstrated promising results with the combination of BPD-mediated PDT combined with PDL irradiation. We then initiated clinical translation of the protocol in a Phase I FDA approved trial of PDT+PDL for treatment of PWS [92] and demonstrated that PDT+PDL is more effective for selective removal of cutaneous microvasculature, as compared to PDL alone.…”
Section: Development Of New Treatment Approachesmentioning
confidence: 99%
“…Additional antivascular approaches include photodynamic therapy (PDT)18192021, embolotherapy22232425, antivascular ultrasound therapy (AVUT)262728, and photothermolysis29. These approaches have been developed to shut down or destroy existing blood vessels.…”
mentioning
confidence: 99%